The moderating effect of the board independence on the association between ESG reporting and financial distress - Almutairi, Abdullah; Alayed, Tasneem; Mohammed, Ismail Gaballah Abas; Elmashtawy, Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
This research reveals the influence of ESG reporting on financial distress. Moreover, the study examines the moderating influence of board independence between ESG reporting and the financial distress of the Saudi Arabian Exchange. The study used a database of 432 observations from non-financial corporations on the Saudi stock exchange from 2018 to 2023, employing fixed effect models to estimate the study findings. The study results indicate that ESG reporting enhances financial distress. Companies that have ESG reporting are associated with higher financial distress. Furthermore, the results reveal that board independence moderates the nexus between ESG reporting and financial distress. The study’s originality resides in exploring the moderating role of board independence on the association between ESG reporting and financial distress, utilizing a sample from Saudi companies. This research offers companies, policymakers, and stakeholders practical insights to mitigate financial distress. The study encourages companies to adopt ESG reporting, thereby enhancing their financial performance.